Filtration Performance and Fiber Shedding Behavior in Common Respirator and Face Mask Materials - Qingfeng Cao; Seong Chan Kim; Qisheng Ou; Hoo Young Chung; Weiqi Chen; William Durfee; Susan Arnold; Marc A. Hillmyer; Linsey A. Griffin; David Y. H. Pui (Aerosol and Air Quality Research)
Abstract Wearing respirators and face masks is effective for protecting the public from COVID-19 infection. Thus, there is a need to evaluate the performance of the commonly used respirators and face masks. Two experimental systems were developed to investigate seven different mask materials, which have a fiber size range from 0.1 µm (100 nm) to 20 µm (20,000 nm). One of the systems is a computer-controlled setup for measuring the filtration performance, including size-dependent filtration efficiency and pressure drop, while the other system is for testing the fiber shedding behavior of the materials. The technique of scanning electron microscope (SEM) was applied to observe the dimensions and structures of those materials, which are made of nonwoven-fabrics electret-treated media, cotton woven fabrics, or nanofiber media. The study indicated that the 3M N95 respirator has the best overall filtration performance with over 95% efficiency and low pressure drop of 74.1 Pa. The two commercial cotton face masks have the worst filtration performance in general, with a filtration efficiency of around 25%. No broken fibers from by the seven tested respirator and face mask materials were discovered; however, dendrite structures likely shed by the SHEMA97 face mask with a size comparable to its nanoscale fibers were identified. The reason for this phenomena is presented.